O desenvolvimento do psiquismo na perspectiva do professor de arte: contribuições da Psicologia Histórico-Cultural - Biavatti, Sandra Macanhão (2021)
This research is based on the perspective of the Cultural-historical Psychology, for being the one which best explains the psychic development and the role of the school in this process. The aim was to investigate what the comprehension of the Arts teachers is, concerning the concepts of the development of the psychism and its relation with the superior psychological functions, besides reflecting upon the consequences of such conception in the pedagogical praxis. With this goal, a field research was developed involving 15 Arts teacher from state public schools in the city of Cascavel, state of Paraná, who correspond to 44% of the permanent Arts teachers who act in the researched city. Data were collected in 2019 through a handwritten-filled form, individualized and handed in person. Only 6% of the teachers verbalized a concept of psychic development coherent to what is proposed by the Cultural-historical Psychology; 47% brought some fragmented elements referring to this concept and 47% of the teachers did not know or presented only fragments of ideas far off the concept; that means, about half of the Arts teachers were totally unaware of it. Regarding the concept of superior psychological functions, 73% of the researched teachers did not know about it, 20% showed some fragmented elements of this concept and 6% expressed it accurately. The reflection upon the results of the research reveals, thus, the absence of collective discussions about these concepts in the school environment. If the word is not spread out, it does not impact human being, it is not appropriated by them and does not form concepts. For these concepts to be appropriated, it would be necessary to discuss them collectively, making the objectification of reflections on the Cultural-historical Psychology possible, based on the contributions of the Cultural-historical Psychology. This research also sought to verify which the consequences for the pedagogical process are, concerning the observed lack of appropriation of the concepts, investigating the material used by the teachers for the preparation of their classes, their pedagogical actions, as well as their limitations and challenges. It was observed an absence of intention in the pedagogical process in the sense of promoting the humanization of the senses and the aesthetic sensibility. The lack of consciousness about the role of the teacher in this process plus the dissociation between theory and practice contribute to the indiscipline, disinterest and absent-mindedness on the student’s side. Inadequate conditions were verified regarding competence of the State, such as lack of materials and technological resources, as well as physical spaces proper to the Arts classes. Pedagogical difficulties were observed due to the fact that the subject demands a teacher who masters the four artistic languages: Visual Arts, Theater, Music and Dance, whilst the initial formation approaches only one of these. Moreover, there is a clear need for the State to promote continuous training through courses or study groups in the school, focused on the development of the theoretical thinking, considering the Study Activity as an important alternative for teaching Arts, as a way of overcoming this need and promoting the reflection upon the teaching work, using the theoretical-practical fundament of the Cultural-historical Psychology as basis. This way, the teacher will be able to plan and implement tasks, carrying out a significant learning through the intercession of the contents in an organized way, aiming to provide students consciousness when observing a piece of art, develop their creativity, making sense of the historical meaning and the importance of understanding and representing reality through artistic languages, promoting development of the psychism through learning. As a conclusion, it is possible to understand that the pedagogical work in school must go beyond the everyday concepts, enabling students to appropriate scientific concepts and, in this process, develop their superior psychological functions, among which the creative imagination, the theoretical and aesthetic-artistic thinking, in a way that makes it possible for them to instrumentalize themselves for some reading and consequent action to transform reality. However, it is arguable how the teachers who did not have such formation will be able to play the role of mediator in the development of their students’ personality as demanded by the appropriation of the theoretical thinking. It is observed that the issue is not individual, but a social problem, which demands the State to carry out conditions for the human generic development, in which the Arts promote the cultural and creative transformation in the teachers and students in the sense of the humanization. Therefore, in the opposite direction of the dehumanizing barbarism that rapidly takes over, where the man is just a resource for the capital.